2016
DOI: 10.1002/app.43797
|View full text |Cite
|
Sign up to set email alerts
|

In situ fibrillation of poly(trimethylene terephthalate) in polyolefin elastomer through multistage stretching extrusion

Abstract: Polyolefin elastomer (POE)/poly(trimethylene terephthalate) (PTT) microfibrillar composites (MFCs) were successfully fabricated by multistage stretching extrusion with an assembly of laminating‐multiplying elements (LMEs). The morphologies of these novel materials were greatly influenced by the compositions. The number of microfibrils increased with increasing PTT concentration, as revealed by scanning electron microscopy. The tensile strength was the highest along the extrusion direction at the weight ratio o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…The in situ microfibrillar composites with iPP as matrix and x-PA66 as dispersed fibrils were fabricated through multistage stretching extrusion with an assembly of laminatingmultiplying elements (LMEs), the mechanism of which has been described in other literatures. [23][24][25] iPP and x-PA66 pellets with constant weight ratio of 85/15 were firstly dry-mixed in a high-speed mixer, then went through the two-screw extruder, connector, LMEs, and finally formed a sheet about 0.4 mm thick and 300 mm wide. The temperature profile from feed section to metering section of the twin-screw extruder was set at 150 C, 260 C, 265 C, 275 C, respectively.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…The in situ microfibrillar composites with iPP as matrix and x-PA66 as dispersed fibrils were fabricated through multistage stretching extrusion with an assembly of laminatingmultiplying elements (LMEs), the mechanism of which has been described in other literatures. [23][24][25] iPP and x-PA66 pellets with constant weight ratio of 85/15 were firstly dry-mixed in a high-speed mixer, then went through the two-screw extruder, connector, LMEs, and finally formed a sheet about 0.4 mm thick and 300 mm wide. The temperature profile from feed section to metering section of the twin-screw extruder was set at 150 C, 260 C, 265 C, 275 C, respectively.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…As schematically shown in Figure , when the polymeric melt enters into a LME, the flowing behavior can be described as follows: (1) dividing, the melt is first sliced into left and right parts; (2) stretching, the left and right parts then enters into two fish‐tail ducts, respectively, in which a strong shearing and elongational forces have been imposed on the melt; (3) multiplying, the two parts integrate into one at the exit of LME. An array of elaborate work launched by our research group indicated that LME could transform the spherical phase morphology into microfibrillar, which provided an effective route to obtain MFCs …”
Section: Introductionmentioning
confidence: 99%
“…Recently, in situ brillation of polymer blend, which converts the dispersed particles into micro-or nano-brillar structure, has attracted much attention. [3][4][5][6][7][8] Owing to the exibility and high aspect ratio, the brils can deform adequately in response to interbrillar interactions during ow. 9 When the brils concentration exceeds a certain value, the deformed brils can form a physical network structure which renders the blends excellent properties.…”
Section: Introductionmentioning
confidence: 99%
“…The enhanced melt elasticity is very important for some processing such as blow molding and foaming, where biaxial strength is needed. 11 Dong et al 6 observed that the poly(trimethylene terephthalate) (PTT) microbrils had a greater inuence on the rheological properties of polyolen elastomer (POE) than PTT particles because the PTT microbrils could form a physical network within the POE matrix. Zhao et al 10 and Wang et al 8 prepared in situ MFCs with different methods and measured the effects of dispersed phase concentration on the complex viscosity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation